Let be a strictly increasing function such that for all natural numbers . Find the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If f ( 1 ) = 1 then f ( f ( 1 ) ) = 1 but f ( f ( 1 ) ) = 3 , so f ( 1 ) isn't equal to 1 If f ( 1 ) > 2 then f ( 2 ) > 3 , so f ( f ( 1 ) ) > 3 , but f ( f ( 1 ) ) = 3 , so f ( 1 ) isn't greater than 2
Thus f ( 1 ) = 2 , and f ( 2 ) = 3 . Similarly, it follows that f ( 3 ) = f ( f ( 2 ) ) = 6 , and f ( 6 ) = f ( f ( 3 ) ) = 9 , so 9 > f ( 5 ) > f ( 4 ) > 6 , so f ( 5 ) = 8 and f ( 4 ) = 7 .
Now we have found the following:
f ( 1 ) = 2 , f ( 2 ) = 3 , f ( 3 ) = 6 , f ( 4 ) = 7 , f ( 5 ) = 8 , f ( 6 ) = 9
Through induction, it is simple to prove that f ( 3 n ) = 2 × 3 n and that f ( 2 × 3 n ) = 3 n + 1 .
Since f ( n ) is a strictly increasing function f ( n + 1 ) ≥ f ( n ) + 1 . This further implies that f ( n + m ) ≥ f ( n ) + m .
We thus have that f ( 3 n + k ) (where 3 n ≥ k ≥ 0 ) 2 × 3 n + k = f ( 2 × 3 n ) − ( 3 n − k ) ≥ f ( 3 n + k ) ≥ f ( 3 n ) + k = 2 × 3 n + k
Thus f ( 3 n + k ) = 2 × 3 n + k where 3 n ≥ k ≥ 0 . It also follows that f ( 2 × 3 n + k ) = 3 n + 1 + 3 k where 3 n ≥ k ≥ 0
Since f ( 2 0 0 1 ) = f ( 2 × 7 2 9 + 5 4 3 ) = f ( 2 × 3 6 + 5 4 3 ) = 3 7 + 3 × 5 4 3 = 3 8 1 6